2019
DOI: 10.1155/2019/7960268
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-Resistant Bacteria from Raw Meat of Buffalo and Chicken, Nepal

Abstract: Antimicrobial resistance is a major global issue for human and animals. Increased use of antimicrobials in livestock and poultry has become one of the causes of antimicrobial resistance development in microorganisms. The aim of the study was to characterize antimicrobial resistant bacteria from raw buffalo and chicken meat in standard in vitro condition. A total of 140 raw meat samples were collected from different retail shops of Bhaktapur Metropolitan City, Nepal. Among them, 70 were raw buffalo meat and 70 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
37
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 31 publications
18
37
1
Order By: Relevance
“…Among SXT resistant E. coli isolates of animal origin, ampicillin and tetracycline have been identified in previous studies as common cotransferred resistant phenotypes [29]. The MDR rate of 22% in E. coli isolates was similar to studies carried out by Saud et al on raw buffalo meat while significantly higher rates were observed for chicken in the same study [30]. These findings can be attributed to the routine use of antibiotics in poultry feed and less common use of oral antibiotics in large animals.…”
Section: Discussionsupporting
confidence: 82%
“…Among SXT resistant E. coli isolates of animal origin, ampicillin and tetracycline have been identified in previous studies as common cotransferred resistant phenotypes [29]. The MDR rate of 22% in E. coli isolates was similar to studies carried out by Saud et al on raw buffalo meat while significantly higher rates were observed for chicken in the same study [30]. These findings can be attributed to the routine use of antibiotics in poultry feed and less common use of oral antibiotics in large animals.…”
Section: Discussionsupporting
confidence: 82%
“…The present study reports the first comprehensive findings on the extent and distribution of ESBL-Ec and their antimicrobial resistance pattern including resistance genes in frozen chicken meat collected from almost all branded supershops located in five megacities of Bangladesh. This study showed the high prevalence (76.1%) of E. coli in frozen chicken meat compared with 49-53% prevalence in raw chicken meat as reported earlier in Bangladesh [30,31], 66.3% in India [32], 47.1% in Nepal [33], and 50.5% in Korea [34], and this may be a potential hazard to the consumers. The difference in the prevalence of E. coli may be attributed to several factors including the source of meat, sample number, isolation methods, possible cross-contamination during slaughtering, slaughterhouse sanitation, and personal hygiene, as well as other practices through to the food chain.…”
Section: Discussionsupporting
confidence: 74%
“…Among SXT resistant E. coli isolates of animal origin, ampicillin and tetracycline have been identi ed in previous studies as common co-transferred resistant phenotypes (29). The MDR rate of 22% in E. coli isolates was similar to studies carried out by Saud et al on raw buffalo meat while signi cantly higher rates were observed for chicken in the same study (30). These ndings can be attributed to the routine use of antibiotics in poultry feed and less common use of oral antibiotics in large animals.…”
Section: Discussionsupporting
confidence: 83%